Activity of Trimethylamine-N-Oxide Demethylase (TMAOase) in the Forming of Natural Formaldehyde in Lizardfish (Saurida tumbil) - Azizah Nuraini; Tati Nurhayati; Mala Nurilmala (Jurnal Pengolahan Hasil Perikanan Indonesia, 2017)
Formaldehyde found in the fish has been occurred naturally through the work of trimethylamine-N-Oxide demethylase (TMAO)ase enzyme that broke TMAO into formaldehyde and dimethylamine.Formaldehyde found in fish has been occurred during storage. This reserch was aimed to determine theTMAOase activity and its role in dimethylamine and formaldehyde formation in Greater lizardfish (Sauridatumbil), which stored at chilling temperature. Observations were made every 2 days for 16 days of storage.Analysis performed in formaldehyde content determination, dimethylamine content determination, andspecific activity of TMAOase enzyme. The result of formaldehyde test was increasing during storage, from0,22±0,00 ppm on day 0 to 7,45±0,46 ppm on day 16. The results of dimethylamine test increased duringstorage from 0,93±0,50 ppm at day 0 to 27,26±1,8 ppm on day 16. The results of TMAOase specific activityin Greater lizardfish increased during storage from 1,15 U/mg on day 0, to 16,47 U/mg on day 16.